2001
DOI: 10.1002/1522-7278(2001)16:1<84::aid-tox100>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dissolved carbon dioxide on the physiology and behavior of fish in artificial streams

Abstract: A new technology for treating waters contaminated with acid mine drainage involves the dissolution of limestone particles using carbon dioxide at pressures above ambient. Because of the fish health risks associated with episodes of high carbon dioxide levels in treated waters, we subjected three species of fish, brook trout (Salvelinus fontinalis), slimy sculpin (Cottus cognatus), and blacknose dace (Rhinichthys atratulus), to 24 h exposures of elevated dissolved carbon dioxide (CO2) at three levels, ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…A similar D r a f t approach was conducted by Kates et al (2012), where avoidance responses were documented from silver carp, bluegill (Lepomis macrochirus), and largemouth bass (Micropterus salmoides) at concentrations ≥ 100 mg/L CO 2 . Further, blacknose dace (Rhinichthys atratulus) and brook trout (Salvelinus fontinalis) exhibited avoidance behavior when exposed to 120 mg/L CO 2 in small laboratory tanks (Ross et al 2001). When in our outdoor pond, we observed similar avoidance behavior of silver and bighead carp at concentrations around 70 mg/L CO 2 and found that this technique could potentially be used to deter upstream movement.…”
Section: Discussionsupporting
confidence: 53%
“…A similar D r a f t approach was conducted by Kates et al (2012), where avoidance responses were documented from silver carp, bluegill (Lepomis macrochirus), and largemouth bass (Micropterus salmoides) at concentrations ≥ 100 mg/L CO 2 . Further, blacknose dace (Rhinichthys atratulus) and brook trout (Salvelinus fontinalis) exhibited avoidance behavior when exposed to 120 mg/L CO 2 in small laboratory tanks (Ross et al 2001). When in our outdoor pond, we observed similar avoidance behavior of silver and bighead carp at concentrations around 70 mg/L CO 2 and found that this technique could potentially be used to deter upstream movement.…”
Section: Discussionsupporting
confidence: 53%
“…Since a similar level of P CO 2 was used in these studies, the relationship of growth suppression and ambient CO 2 levels cannot be determined. High CO 2 appears to reduce foraging activity, thereby decreasing growth [ Crocker and Cech , 1996; Ross et al , 2001; Foss et al , 2003]. There are also some indications that CO 2 suppresses taste nerve responses to taste stimulants in Japanese eel [ Yoshii and Yotsui , 1997].…”
Section: Physiological Effects Of Co2 On Fishmentioning
confidence: 99%
“…Additionally, prior experimental evaluations have assessed the effects of fish density in nets and holding containers and their association with increases in glucose and cortisol concentrations (Wedemeyer 1976;Gomes et al 2003). Changes in water quality parameters during transportation, such as dissolved oxygen (Caldwell and Hinshaw 1994;Evans et al 2003), ammonia (Randall and Tsui 2002;Wicks and Randall 2002;Barbieri and Bondioli 2015), carbon dioxide (Ross et al 2001), and salinity (Bosisio et al 2017) can lead to increased fish glucose and cortisol concentrations, and in some instances, mortality. However, to understand the effects of transportation practices on fish, simultaneous monitoring of changes in water chemistry, fish physiology, and handling techniques are necessary (Barton et al 1985;Evans et al 2003;Gomes et al 2003).…”
Section: Introductionmentioning
confidence: 99%